Same place, same knowledge - same people? The geography of non-patent citations in Dutch polymer patents - Dominik Heinisch; Önder Nomaler; Guido Buenstorf; Koen Franken; Harry Lintsen (Philipps-University Marburg, School of Business and Economics, 2015)
It has long been argued that geographic co-location supports knowledge spillovers. More recently, this argument has been challenged by showing that knowledge spillovers mainly flow through social networks, which may or may not be localized at various geographic scales. We further scrutinize the conjecture of geographically bounded knowledge spillovers by focusing on knowledge flows between academia and industry. Looking into citations to non-patent literature (NPL) in 2,385 Dutch polymer patents, we find that citation lags are shorter on average if Dutch rather than foreign NPLs are cited. However, when excluding individual and organizational self-citations, geographically proximate NPLs no longer diffuse faster than foreign NPLs. This suggests that knowledge is not "in the air" but transferred by mobile individuals and/or direct university-industry collaboration. Our findings moreover suggest an important role of international conferences in the diffusion of recent scientific knowledge.
Keywords: O33; R10; L65; 330; non-patent literature; citation lags; knowledge spillovers; university-industry interaction; polymer industry